Parental media of natural diamonds and primary mineral inclusions in them: Evidence from physicochemical experiment - Litvin, Y.; Vasilyev, Prokopiy; Bobrov, A.; Okoemova, V.; Kuzyura, A. (2012)
A generalized diagram was constructed for the compositions of multicomponent heterogeneous parental media for diamonds of kimberlite deposits on the basis of the mantle carbonatite concept of diamond genesis. The boundary compositions on the diagram of the parental medium are defined by the components of minerals of the peridotite and eclogite parageneses, mantle carbonatites, carbon, and the components of volatile compounds of the C-O-H system and accessory phases, both soluble (chlorides, phosphates, and others) and insoluble (sulfides and others) in carbonate-silicate melts. This corresponds to the compositions of minerals, melts, and volatile components from primary inclusions in natural diamonds, as well as experimental estimations of their phase relations. Growth media for most natural diamonds are dominated by completely miscible carbonate-silicate melts with dissolved elemental carbon. The boundary compositions for diamond formation (concentration barriers of diamond nucleation) in the cases of peridotite-carbonate and eclogite-carbonate melts correspond to 30 wt % peridotite and 35 wt % eclogite; i.e., they lie in the carbonatite concentration range. Phase relations were experimentally investigated at 7 GPa for the melting of the multicomponent heterogeneous system eclogite-carbonatite-sulfide-diamond with a composition close to the parental medium under the conditions of the eclogite paragenesis. As a result, “the diagram of syngenesis” was constructed for diamond, as well as paragenetic and xenogenic mineral phases. Curves of diamond solubility in completely miscible carbonate-silicate and sulfide melts and their relationships with the boundaries of the fields of carbonate-silicate and sulfide phases were determined. This allowed us to establish the physicochemical mechanism of natural diamond formation and the P-T conditions of formation of paragenetic silicate and carbonate minerals and coexistence of xenogenic sulfide minerals and melts. Physicochemical conditions of the capture of paragenetic and xenogenic phases by growing diamonds were revealed. Based on the mantle carbonatite concept of diamond genesis and experimental data, a genetic classification of primary inclusions in natural diamond was proposed. The phase diagrams of syngenesis of diamond, paragenetic, and xenogenic phases provide a basis for the analysis of the physicochemical history of diamond formation in carbonatite magma chambers and allow us to approach the formation of such chambers in the mantle material of the Earth.